Identitas dan Akal Budi Manusia: Signifikansi Konsep Kovenan Johan Herman Bavinck dalam Konteks Pluralisme - Doni Herwanto Harianja (Verbum Christi: Jurnal Teologi Reformed Injili, 2023)
This research aims to analyse the concept of covenant according to the thoughts of Johan Herman Bavinck in responding to the situation of religious diversity in Indonesia. In the author's observation, the religious diversity situation in Indonesia continues to be a subject of controversy. The presence of followers of a particular religion is perceived as a threat to followers of other faiths. Relations among religious followers tend to breed suspicion. Moreover, in the context of religion, individuals also tend to struggle to think clearly when addressing such situations. The author argues that issues of human identity and rationality amid the religious diversity situation in Indonesia can be mediated and understood through the concept of covenant. Thus, through this writing, the author aims to demonstrate that the covenant concept can be used as a framework for understanding life as a Christian amidst religious diversity in Indonesia and addressing intolerant conditions where injustice may arise in society.